Hydrolytically stable MOF in 3D-printed structures - Halevi, Oded (2020)
Metal–organic frameworks (MOFs) are a well‐developed field of materials, having a high potential for various applications such as gas storage, water purification, and catalysis. Despite the continuous discoveries of new MOFs, so far there are only a limited number of industrial applications, partially due to their low chemical stability and limited mechanical properties, as well as difficulties in integration within functional devices, Herein, a new approach is presented toward the fabrication of MOF‐based devices, utilizing direct 3D printing. By this method, 3D, flexible, and hydrolytically stable MOF‐embedded polymeric structures are fabricated. It is found that the adsorption capacity of the 3D‐printed MOF is retained, with significantly improved hydrolytic stability of the printed MOFs (copper benzene‐1,3,5‐tricarboxylate) compared to the MOF only. It is expected that applying 3D printing technologies, for the fabrication of functional MOF objects such as filters and matrices for columns and flow reactors, will open the way for utilization of this important class of materials.